Implication of Regulation Authorities on the Efforts to Accelerate the Eradication of Corruption - Sukmareni, Sukmareni; Danil, Elwi; Ismansyah, Ismansyah; Daulay, Zainul (Faculty of Law, Hasanuddin University, 2018)
Investigation of corruption, as an extra ordinary crime is granted to the three institutions, namely the Police, Attorney General and the Indonesian Corruption Eradication Commission (KPK). The granting of authority to these three institutions aims to accelerate the eradication of corruption, not only detrimental to the finances and the economy of the country but has damaged the joints of life of the nation and state. The research is descriptive and uses a normative juridical approach. Aiming to find out, and analyze qualitatively the implications of regulating investigative authority over the eradication of corruption in Indonesia. The study found that all three institutions that were given the authority to investigate corruption crimes were administratively separated, but functionally these three institutions should collaborate to accelerate the eradication of corruption, but in practice this was not the case, each institution tended to be shackled by fragmentary and institutional nature. centric that does not support the eradication of corruption. This is because the regulation of the authority of each institution has not been strictly regulated, then the arrangements are not synchronized and among the existing legislation, so that there is overlap of authority due to differences in interpretation between investigators, which results in investigations not going well.